Climatic Design of Iranian Traditional Buildings Case Study: Tabriz - Neghabi, Mahboobe (IJRDO-Journal of Applied Science, 2016)
Today, the environment, saving fossil energy and sustainable development have becomeimportant and common discussions at the international level. So that energy sources'conservation, avoiding contaminating the land and the environment, reducing the amount offossil energy consumption and coexistence with natural and climate conditions have become oneof the most important measures in architecture and urbanism. In modern discussions ofsustainable architecture, the use of passive systems for cooling and heating of buildings is a wayof saving energy consumption. On the other hand, Iran's traditional architecture in the residentialsector and in the non-residential sector, as well as the integration of these two broadly in thename of the city has unique features that while considering aesthetic issues and the environmentconservation has also been responsive to climate needs of each region. Techniques and rulesused in this architecture have many new concepts in the field of sustainable architecture in itselfclearly that the paper examined these concepts in Tabriz residential architecture located in coldregions of Iran. The method of the present paper is descriptive-analytic and data collectionmethod is library and field. In this paper, the traditional solutions for cooling and heating intraditional architecture were classified in the form of passive cooling and heating methods andfinally the result was that most of proposed methods have been considered in passive systems oftraditional architecture and by detailed study of Iran architecture, urban development andmodernization intelligent solutions can be found matching local architecture of regions.